EMPOWERMENT UMKM BANDAR LAMPUNG MELALUI PROGRAM E-CASM (E-COMMERCE AND SOCIAL MEDIA) SEBAGAI UPAYA PERLUASAN PASAR GUNA MENINGKATKAN PENDAPATAN UMKM - Oktavia, Reni; Alvia, Liza; Gustiawaty Dewi, Fajar; Evana, Einde (Faculty of Economics and Business Lampung University, 2024)
This activity discusses how MSMEs use e-commerce and social media to market their products. Through this activity, it is hoped that it can create a wider market share so that it can increase the income of MSME players. Apart from that, at the same time, MSMEs are becoming more innovative and creative in developing their businesses. The target of this activity is MSMEs in 7 sub-districts of Bandar Lampung City who are still not utilizing e-commerce and social media and are ready to develop their businesses more widely using digital platforms. The method used consists of 3 stages, namely the preparation stage, process stage and evaluation stage. The benefit of this activity is to provide knowledge to MSME players about the use of e-commerce and social media. This activity will also provide an opportunity for MSMEs to network with other business actors and learn from their experiences. Participants will be given hands-on training on how to use e-commerce platforms and social media to market their products. So the expected output is that participants can better understand the use of e-commerce and the role of digital marketing through social media